Challenging Representations of Sámi Characters in Fiction for Young Readers - Palo, Annbritt; Manderstedt, Lena; Kokkola, Lydia (Barnboken, 2023)
This study focuses on challenging representations of Sámi characters and cultures in Swedish literary works for young readers: “Bamse möter Stallo” (Bamsy Meets Stállu, 2021), a cartoon intended for pre-literate and young readers, Lilli, Lávre och Saivofolket (Lilli, Lávre and the Sáivu People, 2021), a picturebook, and När vi var samer (When We Were Sámi, 2021), a graphic novel accessible for teenagers. The aim is to map how the Sámi characters and cultures are presented and represented, and by and for whom, using critical race theory. The research questions are: 1) How do verbal and visual elements in the analysed works contribute to the representations of the Sámi characters and cultures? 2) How might the critical race theory framework be relevant in the Swedish-Sámi context? The findings show how authors and illustrators use symmetrical, enhancing, complementary, or counterpointing interplay to pinpoint preconceived notions of Sáminess, inform the readers about historical and contemporary racism, challenge underlying perceptions that privilege Swedishness, and to tell stories and counter stories about Sápmi, the Sámi peoples, and Sámi cultures. Validerad;2024;Nivå 1;2024-01-01 (hanlid); Full text license: CC BY